Voluntad, libertad, libre albedrío y libertinaje: Necesidades ecosóficas urgentes - Rodríguez, Milagros Elena (Revista Albertus Magnus, 2022)
It is a complex transparadigmatic transmethodical investigation, with the complex objective of analyzing the constructs will, freedom, free will and debauchery as urgent ecosophical needs. In the line of research: transepistemologies of knowledge-knowledge and transcomplex transmethodologies; antigenealogy of modernist-postmodernist-colonial inquiries; the research subject being in the first person refuting, contributing with his feeling to think; beyond static and reductionist divisions. With the transmethod: the comprehensive, ecosophical and diatopical hermeneutics rhizomatically intertwined in the analytical, empirical and propositional moments. At the propositive moment, beyond finished conclusions, we discern that even when sin has invaded us, let us not forget the creation wonderfully recounted in Genesis: it is urgent and that is an ecosophical need: to examine ourselves, unravel the type of seed that we coexist with . Do we have the freedom for such a cogitative mission? I think so, conceiving that philosophy is not separated from theology, nor from science.